A V-Ti wear-resistant steel with a hardness of HB550-600 and a production method thereof

By refining the V-TI out of the low-temperature return Hua Jones substrate and optimizing the steel plate composition and organization in combination with multi-stage process, the problem of high hardness and abrasion resistance and other performance contradictions are solved, and high hardness and strong toughness are achieved. And well -welded abrasion -resistant steel.

CN116254480BActive Publication Date: 2025-01-28YANCHENG LIANXIN IRON & STEEL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310227136.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-06
Publication Date
2025-01-28
Estimated Expiration
2043-03-06

AI Technical Summary

Technical Problem

When the hardness of existing high-hard wear-resistant steel exceeds HB500, the plastic toughness of the steel plate will decrease sharply, the wear-resistant performance is difficult to improve, and the processing performance is deteriorated, which will not effectively solve the contradiction between hardness and other performance.

Method used

By refining the size of the V-TI output phase in the low-temperature return Hua Jones substrate to 5-15nm, the nano-level precipitation accounts for 40-50 % of the total analysis volume. Rh vacuum treatment, linked into blank, rolling and quenching, etc., optimize the chemical composition and micro tissue structure of steel plates.

Benefits of technology

The strong toughness and welding performance of high-hardness and wear-resistant steel have been achieved. The hardness is HB550 ~ 600, the tensile strength ≥1900MPa, the extension A ≥ 7 %, and-40 ° C impact ≥30J, which meets the application requirements of high-end users. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116254480B_ABST
    Figure CN116254480B_ABST
Patent Text Reader

Abstract

A V-Ti wear-resistant steel with a hardness of HB550-600, the chemical composition and weight percent of which are: C: 0.25-0.45%, Mn: 0.80-1.20%, Gr+Mo: 0.55-0.95%, V+Ti: 0.25-0.44%, P≤0.015%, S≤0.0025%, N≤0.0045%, O≤0.0015%; the production method comprises the following steps: LF refining after converter smelting; RH vacuum treatment; continuous casting into billets; heating of the billets; rough rolling in the recrystallization zone; finish rolling in the non-recrystallization zone; cooling; off-line quenching; low-temperature tempering; and standby. The size of V and Ti precipitated phases of the present invention is refined to 5-15 nm, the 5-15 nm nanoscale precipitated phase accounts for 40-50% of the total precipitated amount, the tensile strength is ≥1900 MPa, the hardness is HB550-600, the elongation A is ≥7%, and the impact energy at -40°C is ≥30 J, which meets the needs of high-end users.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to wear-resistant steel for engineering machinery and a production method thereof, in particular to V-Ti-containing wear-resistant steel with a hardness of HB550-600 and a production method thereof. Background Art

[0002] High-hardness wear-resistant steel is widely used in mechanical products such as mining, construction, cement production, ports, electricity, and metallurgy. The purpose is to slow down the wear rate of mechanical parts and extend the time before failure due to wear.

[0003] High hardness is the premise of improving the wear resistance of wear-resistant materials. Foreign advanced wear-resistant steel varieties mainly include Sweden's SSAB's HARDOX series and SB series, Germany's Dillingen V series and ThyssenKnuber XRA series, Japan's JFE-EH series and Finland's RAEX series, etc., with a hardness of no more than HB500.

[0004] The production and processing technology of wear-resistant steel is more flexible. Through appropriate processing technology, austenite, martensite, bainite or composite organization can be obtained, so that it has better wear resistance and comprehensive application performance. Among them, austenite, bainite or composite organization wear-resistant steel has the disadvantages of high alloy content, complex production process, difficult to control organization and uneven organization. Low alloy martensitic wear-resistant steel has obvious advantages. First, the alloy content is low. Generally, low alloy steel is 3%-5%. The main alloy elements include Ni, Cr, Mo, Mn, Si, B, Nb, V, Ti, etc., which are easy to promote and apply; second, the hardened state organization is obtained by multi-element composite alloying, which can control the matching relationship between hardness and toughness in a large range, and the comprehensive performance is good. Generally, the hardness is greater than 400HB, and the impact toughness value can reach 20-40J; third, the hardenability is improved by alloying, and workpieces of different sizes can be hardened, and even air-cooled martensitic organization can be obtained, which simplifies the heat treatment process; fourth, the processing technology of martensitic wear-resistant steel is more flexible, which can be cast, forged, and rolled. Therefore, martensitic wear-resistant steel has broad application prospects and important promotion value.

[0005] In the existing martensitic wear-resistant steel production technology, the method of increasing hardness is basically the same as the method of increasing strength. However, the hardness of the steel plate is proportional to the strength. That is, when the hardness is higher than HB500, the plastic toughness of the steel plate will drop sharply, the wear resistance will be difficult to improve accordingly, and the processing performance will deteriorate. The main reason is that the control method of the chemical composition and microstructure of the steel plate cannot solve the contradiction between hardness and other properties.

[0006] In terms of chemical composition design, in order to improve the hardness of wear-resistant steel, it is generally adopted to increase the C content and add a large amount of alloying elements, such as Ni, Mo, Cr, Mn, Si, W, etc. However, most alloying elements will damage the toughness and plasticity of wear-resistant steel.

[0007] In terms of microstructure, the microstructure of high-hardness wear-resistant steel is currently martensitic. When the C content is high, the proportion of medium-high carbon martensitic microstructure characterized by lamellar structure increases significantly, but this will cause a sharp deterioration in plasticity and toughness. Therefore, the addition of C and other alloying elements must be strictly controlled in high-hardness martensitic wear-resistant steel, and the resulting low hardness problem must be solved by other means.

[0008] The V-Ti microalloying method can theoretically reduce the dependence of high-hardness wear-resistant steel on C and other alloying elements by precipitation of the second phase in the matrix, and can improve the martensitic microstructure, thereby reducing the damage to its toughness and plasticity while improving the hardness of the wear-resistant steel. However, this method depends on the amount, size, morphology and precipitation process of the second phase precipitation. The precipitation process of the V-Ti second phase in the V-Ti microalloyed wear-resistant steel matrix is ​​very complicated. From solidification to heating, rolling and cooling of the ingot, and heat treatment, each process link will affect the precipitation behavior of V-Ti, which will have a serious impact on the amount, size, morphology and martensitic microstructure of the second phase in the wear-resistant steel plate matrix in the final state, and may even deteriorate the performance.

[0009] Chinese patent numbers ZL 201910643283.4 and ZL 202110351110.2 both propose a process method characterized by two-stage controlled rolling-online quenching-offline quenching-low temperature tempering, which controls the precipitation of carbonitrides of microalloying elements on the martensite matrix. The main purpose is to inhibit grain growth through the second phase, thereby improving the toughness of the base material and the heat affected zone of welding. From the results, since the size of the second phase has not been fully refined, that is, the second phase with a diameter of about 10nm accounts for a small amount of the total precipitation, it can only inhibit grain growth to a certain extent, but has no significant effect on improving strength and hardness, which cannot meet certain engineering applications. It is necessary to further optimize the design of the process method to increase the number of nano-sized precipitated phases, thereby further improving the strength and hardness.

[0010] The present invention develops a method for controlling the precipitation of V-Ti in a low-temperature tempered martensitic matrix in view of the composition, organizational design characteristics and performance requirements of V-Ti microalloyed high-hardness martensitic wear-resistant steel, thereby obtaining nano-sized V-Ti precipitation phases to the maximum extent, improving the strength and toughness and welding performance of the wear-resistant steel, and meeting the application requirements of the wear-resistant steel. Summary of the invention

[0011] The present invention aims to overcome the shortcomings of the prior art and provide a V-Ti wear-resistant steel with a V and Ti precipitate phase size refined to 5-15 nm, a nano-scale precipitate phase accounting for 40-50% of the total precipitate amount, a tensile strength of ≥1900 MPa, a hardness of HB550-600, an elongation A of ≥7%, an impact energy of ≥30 J at -40°C, and simple alloy elements and a production method.

[0012] Measures to achieve the above objectives:

[0013] A V-Ti wear-resistant steel with a hardness of HB550-600, the components and weight percentage contents of which are: C: 0.25-0.45%, Mn: 0.80-1.20%, Gr+Mo: 0.55-0.95%, V+Ti: 0.25-0.44%, P≤0.015%, S≤0.0025%, N≤0.0045%, O≤0.0015%, and the rest are Fe and inevitable impurities; the metallographic structure is tempered martensite, and the V+Ti precipitate phase with a size of 5-15nm accounts for 40-50% of the total precipitate.

[0014] Preferably, the weight percentage of V+Ti is 0.28-0.39%.

[0015] Preferably, the weight percentage of the Gr+Mo is between 0.59 and 0.89%.

[0016] Preferably, the weight percentage of Mn is 0.86-1.13%.

[0017] A method for producing V-Ti wear-resistant steel with a hardness of HB550-600, comprising the following steps:

[0018] 1) LF refining is performed after converter smelting, the amount of LF slag is controlled at 12-17 kg / t molten steel, the slag basicity is controlled at 6-10, the total content of FeO+MnO in the slag is controlled at 0.50-1.20%, the thickness of the foam slag is 50-62 mm, and the S in the molten steel is controlled to be ≤0.0025% at the end of refining;

[0019] 2) Perform RH vacuum treatment, during which: the vacuum degree is controlled to be ≤67Pa, the treatment time is 15 to 20 minutes, and at the end of the vacuum treatment, N in the molten steel is controlled to be ≤0.0045%, and O ≤0.0015%;

[0020] 3) Continuous casting: control the superheat of molten steel at 5-15°C, the cooling intensity of the crystallizer at 2.5-3.5L / min·mm, and the water content in the secondary cooling zone at 1.12-1.35kg / t;

[0021] 4) Billet heating: The billet heating temperature is controlled at 1230-1285°C, and the heating time is controlled according to 1-1.3 min / mm billet thickness;

[0022] 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1025-1120°C, and the deformation rate is 2-4s -1 , the cumulative reduction rate is 25-40%;

[0023] 6) Finish rolling in the non-recrystallization zone: the final rolling temperature is controlled at 940-955°C, and the cumulative reduction rate of the last three passes is controlled at 30-40%;

[0024] 7) Cooling, controlling the cooling temperature at 890-930° C. and the cooling rate at 65-85° C. / s;

[0025] 8) Perform offline quenching:

[0026] First, heat to 650-680°C at a heating rate of 6-10°C / min;

[0027] Then heat to 870-890°C at a heating rate of 26-30°C / min, and keep at this temperature for 5-10 minutes;

[0028] 9) Perform low-temperature tempering, with the tempering temperature controlled at 150-200°C and the tempering time controlled at 150-200min;

[0029] 10) Set aside.

[0030] Preferably, the cooling temperature is between 899°C and 923°C, and the cooling rate is between 79°C and 85°C / s.

[0031] Preferably, during the off-line quenching, the heating temperature is controlled at 656-665°C at a heating rate of 6-8°C / min; and then the heating temperature is controlled at 878-890°C at a heating rate of 28-30°C / min, and the holding time is 5-8min.

[0032] Functions and mechanisms of various raw materials and main processes in the present invention

[0033] C: The reason why the present invention controls C to be within the range of 0.25-0.45% is that if its content is lower than the specified value, the hardness will not reach the design target; if it is higher than the specified value, the toughness, welding performance, etc. will deteriorate.

[0034] The reason why the present invention controls Mn to 0.80-1.20%, preferably 0.86-1.13%, is that if its content is lower than the specified value, sufficient strengthening effect will not be achieved; if it is higher than the specified value, it will cause delayed cracks in the welding heat affected zone and deteriorate the welding performance.

[0035] The reason why the present invention controls Gr+Mo to 0.55-0.95%, preferably 0.59-0.89%, is that if its content is lower than the specified value, the hardenability and material hardness will be reduced; if it is higher than the specified value, it will lead to deterioration of toughness, welding performance, etc.

[0036] The reason why the present invention controls V+Ti to 0.25-0.44%, preferably 0.28-0.39%, is that if its content is lower than the specified value, the precipitation strengthening and grain refinement effects will be insufficient; if it is higher than the specified value, large particle inclusions will be formed, reducing toughness.

[0037] The reason why the present invention controls the amount of LF slag to be 12-17 kg / t of molten steel, controls the basicity of slag to be 6-10, controls the total content of FeO+MnO in the slag to be 0.50-1.20%, and the thickness of the foamed slag to be 50-62 mm is that the LF refining process can improve the desulfurization ability of the refining process and control the S content to be less than or equal to 0.0025%. The amount of LF slag is controlled to be 12-17 kg / t, because increasing the amount of slag can accelerate the desulfurization rate and improve the desulfurization effect, but too much slag will make the slag too thick, affecting the reaction between steel slag; the basicity of slag is controlled to be in the range of 6-10, because the higher the basicity of slag, the stronger the desulfurization ability, but the basicity of slag in the LF process is too high, the slag melting performance is poor, and the desulfurization effect is affected instead; the oxidizability of slag is reduced, the sulfur distribution coefficient between slag and steel is significantly improved, and the lower the oxygen content, the better the desulfurization effect, so the total content of FeO+MnO in the slag is controlled to be 0.5-1.2%.

[0038] The reason why the present invention controls the superheat of molten steel at 5-15°C, the cooling intensity of the crystallizer at 2.5-3.5L / min·mm, and the specific water volume in the secondary cooling zone at 1.12-1.35kg / t is to avoid the precipitation and aggregation growth of Ti precipitated particles in the area near the liquidus line.

[0039] The reason why the heating temperature of the ingot is controlled at 1230-1285°C and the heating time is controlled at 1-1.3 min / mm of the ingot thickness is that the heating of the ingot must ensure that V and Ti are fully dissolved. As the temperature decreases during the rolling stage, the dissolved V and Ti will precipitate in large quantities under the influence of deformation induction, and the precipitation amount and size are related to the rolling temperature and deformation rate.

[0040] The invention controls the rough rolling temperature of the recrystallization zone to be between 1025 and 1120°C and the deformation rate to be between 2 and 4s. -1 The cumulative reduction rate is 25-40%; the finishing temperature of the non-recrystallization zone is controlled at 940-955°C, and the cumulative reduction rate of the last three passes is controlled at 30-40%. This is to induce the appropriate precipitation of V-Ti second phase particles through deformation (the precipitation ratio accounts for 15-35% of the total) and avoid their excessive growth.

[0041] The reason why the present invention controls the cooling temperature at 890-930°C and the cooling rate at 65-85°C / s is that the precipitation kinetics of microalloy carbides in steel during the cooling process is widely described by the classical nucleation and growth theory Avrami kinetic equation. Under the dual effects of driving force and element diffusion, the relationship between precipitation amount and time (PTT curve) is "C" type. When the microalloy element is in a supersaturated state, although the precipitation driving force is large at a relatively low temperature stage, it is not conducive to the diffusion of the element due to the low temperature, and at a relatively high temperature, although the diffusion rate of the element is accelerated, the precipitation driving force is relatively low. Therefore, in the post-rolling cooling and heat treatment stage, the second phase precipitation PTT curve in the cooling or heating process is "C" type. After the precipitation phase is precipitated, aggregation and growth will occur as the temperature rises, i.e., the Ostwald ripening process. Therefore, according to the precipitation behavior of V-Ti during cooling and heating, the present invention designs "rapid cooling after rolling (online direct quenching) + heat treatment (offline quenching + low temperature tempering)" to improve the precipitation kinetics of V-Ti and control the size of the precipitated phase.

[0042] First, rapid cooling is performed after rolling (online direct quenching), with the initial cooling temperature at 890-930°C and the cooling rate at 65-85°C / s to inhibit the precipitation of V and Ti during the cooling process (the precipitated V and Ti will dissolve and mature during the subsequent heat treatment heating process), so that V and Ti are in a supersaturated state. Rapid cooling can also retain the deformation energy generated during rolling, providing kinetic conditions for the precipitation of V and Ti in the heat treatment heating stage.

[0043] The reason why the present invention controls the off-line quenching temperature to rise in two stages: firstly, heating to 650-680°C at a heating rate of 6-10°C / min, then heating to 870-890°C at a heating rate of 26-30°C / min, and keeping the temperature at this temperature for 5-10 minutes is to make the supersaturated V and Ti gradually disperse and precipitate as the temperature rises, and will not dissolve and mature, so that the nano-sized precipitate phase can be retained in the subsequent water-cooling quenching process.

[0044] The present invention adopts low temperature tempering, the tempering temperature is 150-220°C, and the tempering time is 150-200min, because low temperature tempering can eliminate quenching stress, improve toughness and plasticity, and nano-scale V and Ti precipitation phases will not aggregate and grow.

[0045] Compared with the prior art, the V and Ti precipitate phases of the present invention are refined to 5-15nm, the 5-15nm nano-scale precipitate phase accounts for 40-50% of the total precipitate amount, the tensile strength is ≥1900MPa, the hardness is HB550-600, the elongation A is ≥7%, and the -40℃ impact energy is ≥30J, which meets the needs of high-end users. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a transmission electron microscope precipitation phase morphology diagram of the present invention. DETAILED DESCRIPTION

[0047] Example 1

[0048] A V-Ti wear-resistant steel with a hardness of HB550-600, wherein the components and weight percentages thereof are: C: 0.26%, Mn: 0.93%, Gr+Mo: 0.56%, V+Ti: 0.34%, P: 0.009%, S: 0.0023%, N: 0.0045%, O: 0.0012%, and the rest are Fe and unavoidable impurities;

[0049] 1) LF refining is carried out after converter smelting, the amount of LF slag is controlled at 12kg / t molten steel, the slag basicity is controlled at 8, the total content of FeO+MnO in the slag is controlled at 0.52%, the thickness of the foam slag is 52mm, and the S in the molten steel is controlled at 0.0023% at the end of refining;

[0050] 2) RH vacuum treatment is performed, during which: the vacuum degree is 66Pa, the treatment time is 16min, and at the end of the vacuum treatment, N: 0.0045%, O: 0.0012% in the molten steel is controlled;

[0051] 3) Continuous casting: control the superheat of molten steel at 6°C, the cooling intensity of the crystallizer at 2.6L / min·mm, and the water content in the secondary cooling zone at 1.15kg / t;

[0052] 4) Billet heating: The billet heating temperature is 1232°C, and the heating time is controlled according to 1.1min / mm billet thickness;

[0053] 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1028°C and the deformation rate is 2.2s -1 , the cumulative reduction rate is 35%;

[0054] 6) Finish rolling in the non-recrystallization zone: the final rolling temperature is 945°C, and the cumulative reduction rate of the last three passes is controlled at 32%;

[0055] 7) Cooling, the cooling temperature is 893°C, and the cooling rate is 66°C / s;

[0056] 8) Offline quenching: First, heat to 655°C at a heating rate of 7°C / min; then heat to 27°C / min at a heating rate of 27°C / min.

[0057] / min to 873℃ and keep at this temperature for 8min;

[0058] 9) Perform low-temperature tempering, the tempering temperature is 156°C, and the tempering time is 162min;

[0059] 10) Set aside.

[0060] After testing, the V and Ti precipitates in this embodiment are refined to nanoscale precipitates of 5 to 15 nm, accounting for 41.2% of the total precipitation amount, the tensile strength is 1915 MPa, the hardness is HB572, the elongation A is 7.2%, the impact energy at -40°C is 34 J, and the steel plate thickness is 16 mm.

[0061] Example 2

[0062] A V-Ti wear-resistant steel with a hardness of HB550-600, wherein the components and weight percentages thereof are: C: 0.45%, Mn: 0.99%, Gr+Mo: 0.78%, V+Ti: 0.42%, P: 0.012%, S: 0.0018%, N: 0.0039%, O: 0.0014%, and the rest are Fe and unavoidable impurities;

[0063] 1) LF refining is carried out after converter smelting, the LF slag amount is controlled at 12kg / t molten steel, the slag basicity is controlled at 10, the total content of FeO+MnO in the slag is controlled at 0.79%, the foam slag thickness is 50mm, and the S in the molten steel is controlled at 0.0018% at the end of refining;

[0064] 2) RH vacuum treatment is performed, during which: the vacuum degree is 67Pa, the treatment time is 20min, and at the end of the vacuum treatment, N: 0.0039%, O: 0.0014% in the molten steel is controlled;

[0065] 3) Continuous casting: control the superheat of molten steel at 5°C, the cooling intensity of the crystallizer at 2.5L / min·mm, and the specific water content in the secondary cooling zone at 1.12kg / t;

[0066] 4) Billet heating: the billet heating temperature is 1230°C, and the heating time is controlled according to 1.0min / mm billet thickness;

[0067] 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1118°C and the deformation rate is 3.8s -1 , the cumulative reduction rate is 33%;

[0068] 6) Finish rolling in the non-recrystallization zone: the final rolling temperature is 952°C, and the cumulative reduction rate of the last three passes is controlled at 38%;

[0069] 7) Cooling, the cooling temperature is 890°C, and the cooling rate is 69°C / s;

[0070] 8) Offline quenching: First, heat to 672°C at a heating rate of 8°C / min; then heat to 29°C / min at a heating rate of 29°C / min.

[0071] Heat to 885°C at 100 °C / min and keep at this temperature for 5 min;

[0072] 9) Perform low-temperature tempering at 151°C and 200 minutes;

[0073] 10) Set aside.

[0074] After testing, the V and Ti precipitates in this embodiment are refined to nanoscale precipitates of 5 to 15 nm, accounting for 50.0% of the total precipitation amount, the tensile strength is 1955 MPa, the hardness is HB595, the elongation A is 7.5%, the impact energy at -40°C is 33 J, and the steel plate thickness is 12 mm.

[0075] Example 3

[0076] A V-Ti wear-resistant steel with a hardness of HB550-600, wherein the components and weight percentages thereof are: C: 0.33%, Mn: 1.20%, Gr+Mo: 0.92%, V+Ti: 0.25%, P: 0.013%, S: 0.0024%, N: 0.0043%, O: 0.0015%, and the rest are Fe and unavoidable impurities;

[0077] 1) LF refining is carried out after converter smelting, the LF slag amount is controlled at 17kg / t molten steel, the slag basicity is controlled at 6, the total content of FeO+MnO in the slag is controlled at 0.95%, the foam slag thickness is 52mm, and the S in the molten steel is controlled at 0.0024% at the end of refining;

[0078] 2) RH vacuum treatment is performed, during which: the vacuum degree is 63Pa, the treatment time is 18min, and at the end of the vacuum treatment, N: 0.0043%, O: 0.0015% in the molten steel is controlled;

[0079] 3) Continuous casting: control the superheat of molten steel at 15°C, the cooling intensity of the crystallizer at 3.5L / min·mm, and the water content in the secondary cooling zone at 1.35kg / t;

[0080] 4) Billet heating: the billet heating temperature is 1285°C, and the heating time is controlled according to 1.3min / mm billet thickness;

[0081] 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1042°C and the deformation rate is 3.1s -1 , the cumulative reduction rate is 31%;

[0082] 6) Finish rolling in the non-recrystallization zone: the final rolling temperature is 949°C, and the cumulative reduction rate of the last three passes is controlled at 40%;

[0083] 7) Cooling, the cooling temperature is 920°C, and the cooling rate is 85°C / s;

[0084] 8) Offline quenching: First, heat to 678°C at a heating rate of 10°C / min; then heat to 29°C / min at a heating rate of 29°C / min.

[0085] / min to 889℃ and keep at this temperature for 8min;

[0086] 9) Perform low-temperature tempering at 198°C and 155 minutes;

[0087] 10) Set aside.

[0088] After testing, the V and Ti precipitates in this embodiment are refined to nanoscale precipitates of 5 to 15 nm, accounting for 42.3% of the total precipitation amount, the tensile strength is 1905 MPa, the hardness is HB588, the elongation A is 7.0%, the impact energy at -40°C is 32 J, and the steel plate thickness is 30 mm.

[0089] Example 4

[0090] A V-Ti wear-resistant steel with a hardness of HB550-600, wherein the components and weight percentages thereof are: C: 0.27%, Mn: 0.82%, Gr+Mo: 0.72%, V+Ti: 0.44%, P: 0.011%, S: 0.0023%, N: 0.0041%, O: 0.0014%, and the rest are Fe and unavoidable impurities;

[0091] 1) LF refining is carried out after converter smelting, the amount of LF slag is controlled at 13kg / t molten steel, the slag basicity is controlled at 7, the total content of FeO+MnO in the slag is controlled at 1.2%, the thickness of the foam slag is 55mm, and the S in the molten steel is controlled at 0.0023% at the end of refining;

[0092] 2) RH vacuum treatment is performed, during which: the vacuum degree is 58Pa, the treatment time is 15min, and at the end of the vacuum treatment, the N content in the molten steel is controlled to be 0.0041% and the O content to be 0.0014%;

[0093] 3) Continuous casting: control the superheat of molten steel at 13°C, the cooling intensity of the crystallizer at 3.3L / min·mm, and the water content in the secondary cooling zone at 1.31kg / t;

[0094] 4) Billet heating: the billet heating temperature is 1235°C, and the heating time is controlled according to 1.2min / mm billet thickness;

[0095] 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1082°C and the deformation rate is 3.8s -1 , the cumulative reduction rate is 32%;

[0096] 6) Finish rolling in the non-recrystallization zone: the final rolling temperature is 952°C, and the cumulative reduction rate of the last three passes is controlled at 39%;

[0097] 7) Cooling, the cooling temperature is 930°C, and the cooling rate is 68°C / s;

[0098] 8) Offline quenching: First, heat to 662°C at a heating rate of 10°C / min; then heat to 26°C / min at a heating rate of 26°C / min.

[0099] / min to 871℃ and keep at this temperature for 6min;

[0100] 9) Perform low-temperature tempering at 186°C and 155 minutes;

[0101] 10) Set aside.

[0102] After testing, the V and Ti precipitates in this embodiment are refined to nanoscale precipitates with a size of 5 to 15 nm, accounting for 48.4% of the total precipitation amount, the tensile strength is 1968 MPa, the hardness is HB582, the elongation A is 7.5%, the impact energy at -40°C is 37 J, and the steel plate thickness is 25 mm.

[0103] Example 5

[0104] A V-Ti wear-resistant steel with a hardness of HB550-600, wherein the components and weight percentages thereof are: C: 0.25%, Mn: 0.92%, Gr+Mo: 0.56%, V+Ti: 0.31%, P: 0.0010%, S: 0.0024%, N: 0.0039%, O: 0.0013%, and the rest are Fe and unavoidable impurities;

[0105] 1) LF refining is carried out after converter smelting, the amount of LF slag is controlled at 14kg / t molten steel, the slag basicity is controlled at 9, the total content of FeO+MnO in the slag is controlled at 0.50%, the thickness of the foam slag is 62mm, and the S in the molten steel is controlled at 0.0024% at the end of refining;

[0106] 2) RH vacuum treatment is performed, during which: the vacuum degree is 64Pa, the treatment time is 19min, and at the end of the vacuum treatment, N: 0.0039%, O: 0.0013% in the molten steel is controlled;

[0107] 3) Continuous casting: control the superheat of molten steel at 12°C, the cooling intensity of the crystallizer at 2.8L / min·mm, and the specific water content of the secondary cooling zone at 1.17kg / t;

[0108] 4) Billet heating: the billet heating temperature is 1281°C, and the heating time is controlled according to 1.0min / mm billet thickness;

[0109] 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1113°C and the deformation rate is 2.9s -1 , the cumulative reduction rate is 31%;

[0110] 6) Finish rolling in the non-recrystallization zone: the final rolling temperature is 951°C, and the cumulative reduction rate of the last three passes is controlled at 36%;

[0111] 7) Cooling, the cooling temperature is 915°C, and the cooling rate is 72°C / s;

[0112] 8) Offline quenching: First, heat to 651°C at a heating rate of 9°C / min; then heat to 29°C / min.

[0113] Heat to 882°C at 100 °C / min and keep at this temperature for 6 min;

[0114] 9) Perform low-temperature tempering at 177°C and 175 minutes;

[0115] 10) Set aside.

[0116] After testing, the V and Ti precipitates in this embodiment are refined to nanoscale precipitates of 5 to 15 nm, accounting for 40.1% of the total precipitation amount, the tensile strength is 1953 MPa, the hardness is HB579, the elongation A is 7.5%, the impact energy at -40°C is 35 J, and the steel plate thickness is 18 mm.

[0117] Example 6

[0118] A V-Ti wear-resistant steel with a hardness of HB550-600, wherein the components and weight percentages thereof are: C: 0.32%, Mn: 1.18%, Gr+Mo: 0.94%, V+Ti: 0.41%, P: 0.008%, S: 0.0019%, N: 0.0038%, O: 0.0014%, and the rest are Fe and unavoidable impurities;

[0119] 1) LF refining is carried out after converter smelting, the amount of LF slag is controlled at 15kg / t molten steel, the slag basicity is controlled at 8, the total content of FeO+MnO in the slag is controlled at 0.69%, the thickness of the foam slag is 57mm, and the S in the molten steel is controlled at 0.0019% at the end of refining;

[0120] 2) RH vacuum treatment was performed, during which: the vacuum degree was 61Pa, the treatment time was 17min, and at the end of the vacuum treatment, N in the molten steel was controlled to be 0.0038%, O to be 0.0014%;

[0121] 3) Continuous casting: control the superheat of molten steel at 9°C, the cooling intensity of the crystallizer at 3.1L / min·mm, and the water content of the secondary cooling zone at 1.28kg / t;

[0122] 4) Billet heating: the billet heating temperature is 1244°C, and the heating time is controlled according to 1.1min / mm billet thickness;

[0123] 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1108°C and the deformation rate is 2.4s -1 , the cumulative reduction rate is 31%;

[0124] 6) Finish rolling in the non-recrystallization zone: the final rolling temperature is 952°C, and the cumulative reduction rate of the last three passes is controlled at 37%;

[0125] 7) Cooling, the cooling temperature is 905°C, and the cooling rate is 69°C / s;

[0126] 8) Offline quenching: First, heat to 667°C at a heating rate of 8°C / min; then heat to 28°C / min at a heating rate of 28°C / min.

[0127] / min to 889℃ and keep at this temperature for 6min;

[0128] 9) Perform low-temperature tempering at 168°C and 192 minutes;

[0129] 10) Set aside.

[0130] After testing, the V and Ti precipitates in this embodiment are refined to nanoscale precipitates with a size of 5 to 15 nm, accounting for 47.2% of the total precipitation amount, the tensile strength is 1935 MPa, the hardness is HB575, the elongation A is 7.4%, the impact energy at -40°C is 38 J, and the steel plate thickness is 22 mm.

[0131] Example 7

[0132] A V-Ti wear-resistant steel with a hardness of HB550-600, wherein the components and weight percentages thereof are: C: 0.38%, Mn: 0.93%, Gr+Mo: 0.62%, V+Ti: 0.38%, P: 0.012%, S: 0.0019%, N: 0.0042%, O: 0.0012%, and the rest are Fe and unavoidable impurities;

[0133] 1) LF refining is carried out after converter smelting, the amount of LF slag is controlled at 16kg / t molten steel, the slag basicity is controlled at 7.5, the total content of FeO+MnO in the slag is controlled at 0.88%, the thickness of the foam slag is 53mm, and the S in the molten steel is controlled at 0.0019% at the end of refining;

[0134] 2) RH vacuum treatment was performed, during which: the vacuum degree was 61Pa, the treatment time was 17min, and at the end of the vacuum treatment, N in the molten steel was controlled to be 0.0042% and O to be 0.0012%;

[0135] 3) Continuous casting: control the superheat of molten steel at 11°C, the cooling intensity of the crystallizer at 2.9L / min·mm, and the specific water content in the secondary cooling zone at 1.33kg / t;

[0136] 4) Billet heating: The billet heating temperature is 1273°C, and the heating time is controlled according to 1.2min / mm billet thickness;

[0137] 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1047°C and the deformation rate is 3.5s -1 , the cumulative reduction rate is 31%;

[0138] 6) Finish rolling in the non-recrystallization zone: the final rolling temperature is 943°C, and the cumulative reduction rate of the last three passes is controlled at 36%;

[0139] 7) Cooling, the cooling temperature is 899°C, and the cooling rate is 71°C / s;

[0140] 8) Offline quenching: First, heat to 658°C at a heating rate of 9°C / min; then heat to 29°C / min.

[0141] / min to 877℃ and keep at this temperature for 8min;

[0142] 9) Perform low-temperature tempering at 156°C and 168 minutes;

[0143] 10) Set aside.

[0144] After testing, the V and Ti precipitates in this embodiment are refined to nanoscale precipitates with a size of 5 to 15 nm, accounting for 47.2% of the total precipitation amount, the tensile strength is 1939 MPa, the hardness is HB586, the elongation A is 7.0%, the impact energy at -40°C is 34 J, and the steel plate thickness is 15 mm.

[0145] This specific implementation is only the best example and is not a restrictive implementation of the technical solution of the present invention.

[0146] Comparative Example 1 (conventional process)

[0147] Its components and weight percentage contents are: C: 0.32%, Mn: 1.18%, Gr+Mo: 0.94%, V+Ti: 0.41%, P: 0.008%, S: 0.0019%, N: 0.0038%, O: 0.0014%, and the rest are Fe and unavoidable impurities;

[0148] 1) Smelting and refining: Control the LF slag amount to 22kg / t, control the slag basicity to 5.5, control the total content of FeO+MnO in the slag to 1.3%, the foam slag thickness to 63mm, during RH vacuum treatment, the vacuum degree is 82Pa, the holding time is 12min, the N content is 0.0052%, and the S content is 0.0028%;

[0149] 2) Continuous casting: molten steel superheat 21 ° C, the cooling intensity of the crystallizer in the continuous casting stage is 3.9L / min·mm, and the water content in the secondary cooling zone is controlled at 1.43kg / t;

[0150] 3) Billet heating: Billet heating temperature 1223 ° C, heating time 0.8 min / mm;

[0151] 4) Controlled rolling: rolling temperature 1130°C, deformation rate 4.5s -1 , the reduction rate of the last three passes is 22%;

[0152] 5) Controlled cooling: cooling temperature 952°C, cooling rate 21°C / s;

[0153] 6) Offline quenching: heating temperature 921°C, holding time 40min;

[0154] 7) Low temperature tempering: tempering temperature is 230℃, tempering time is 140min;

[0155] 8) Set aside.

[0156] After testing, the V and Ti precipitates of this comparative example are refined to nanoscale precipitates of 5 to 15 nm, accounting for 12.1% of the total precipitates, with a tensile strength of 1739 MPa, a hardness of HB522, an elongation A of 6.5%, an impact energy of 17 J at -40°C, and a steel plate thickness of 22 mm.

[0157] Comparative Example 2 (conventional process)

[0158] Its components and weight percentage contents are: C: 0.27%, Mn: 0.82%, Gr+Mo: 0.72%, V+Ti: 0.44%, P: 0.011%, S: 0.0023%, N: 0.0041%, O: 0.0014%, and the rest are Fe and unavoidable impurities;

[0159] 1) Smelting and refining: Control the LF slag amount to 25kg / t, control the slag basicity to 4.5, control the total content of FeO+MnO in the slag to 0.4%, the foam slag thickness to 65mm, during RH vacuum treatment, the vacuum degree is 95Pa, the holding time is 11min, the N content is 0.0055%, and the S content is 0.0038%;

[0160] 2) Continuous casting: molten steel superheat 31 ° C, the cooling intensity of the crystallizer in the continuous casting stage is 3.8L / min·mm, and the water content in the secondary cooling zone is controlled at 1.45kg / t;

[0161] 3) Billet heating: Billet heating temperature 1293 ° C, heating time 1.5min / mm;

[0162] 4) Controlled rolling: rolling temperature 1135°C, deformation rate 4.2s -1 , the reduction rate of the last three passes is 29%;

[0163] 5) Controlled cooling: cooling temperature 880°C, cooling rate 5°C / s;

[0164] 6) Offline quenching: heating temperature 925℃, holding time 40min;

[0165] 7) Low temperature tempering: tempering temperature 220℃, tempering time 120min;

[0166] 8) Set aside.

[0167] After testing, the V and Ti precipitates of this comparative example are refined to nanoscale precipitates of 5 to 15 nm, accounting for 9.1% of the total precipitates, with a tensile strength of 1733 MPa, a hardness of HB512, an elongation A of 6.0%, an impact energy of 14 J at -40°C, and a steel plate thickness of 15 mm.

[0168] The above embodiments are only the best examples and are not intended to limit the implementation of the present invention.

Claims

1. A V-Ti wear-resistant steel with a hardness of HB550-600, wherein the components and weight percentages are: C: 0.25-0.45%, Mn: 0.80-1.20%, Cr+Mo: 0.55-0.95%, V+Ti: 0.25-0.44%, P≤0.015%, S≤0.0025%, N≤0.0045%, O≤0.0015%, and the rest are Fe and unavoidable impurities; the metallographic structure is tempered martensite, and the V+Ti precipitate phase with a size of 5-15nm accounts for 40-50% of the total precipitate; its mechanical properties are as follows: tensile strength ≥1900MPa, elongation A ≥7%, and impact energy at -40℃ ≥30J.

2. A V-Ti wear-resistant steel with a hardness of HB550-600 as claimed in claim 1, characterized in that: The weight percentage of the V+Ti is between 0.28% and 0.39%.

3. The V-Ti wear-resistant steel with a hardness of HB550-600 as claimed in claim 1, characterized in that: The weight percentage of Cr+Mo is between 0.59% and 0.89%.

4. The V-Ti wear-resistant steel with a hardness of HB550-600 as claimed in claim 1, characterized in that: The weight percentage of Mn is 0.86-1.13%.

5. A method for producing a V-Ti wear-resistant steel having a hardness of HB550 to 600 as claimed in claim 1, comprising the steps of: 1) After converter smelting, LF refining is carried out, the amount of LF slag is controlled at 12-17 kg / t molten steel, the slag basicity is controlled at 6-10, the total content of FeO+MnO in the slag is controlled at 0.50-1.20%, the thickness of the foam slag is 50-62 mm, and the S in the molten steel is controlled at ≤0.0025% at the end of refining; 2) Perform RH vacuum treatment, during which: control the vacuum degree ≤67Pa, the treatment time is 15-20 min, and control N≤0.0045% and O≤0.0015% in the molten steel at the end of vacuum treatment; 3) Continuous casting: control the superheat of molten steel at 5-15°C, the cooling intensity of the crystallizer at 2.5-3.5 L / min•mm, and the water content in the secondary cooling zone at 1.12-1.35 kg / t; 4) Billet heating: The billet heating temperature is controlled at 1230-1285°C, and the heating time is controlled at 1-1.3 min / mm billet thickness; 5) Rough rolling in the recrystallization zone: the starting rolling temperature is 1025-1120 °C, and the deformation rate is 2-4 s -1 , the cumulative reduction rate is 25-40%; 6) Finish rolling in the non-recrystallization zone: control the final rolling temperature at 940-955°C, and the cumulative reduction rate of the last three passes at 30-40%; 7) Cooling, controlling the cooling temperature at 890-930°C and the cooling rate at 65-85°C / s; 8) Perform offline quenching: First, heat to 650-680°C at a heating rate of 6-10°C / min; Then heat to 870-890°C at a heating rate of 26-30°C / min, and keep at this temperature for 5-10 minutes; 9) Perform low-temperature tempering, with the tempering temperature controlled at 150-200°C and the tempering time controlled at 150-200min; 10) Set aside.

6. The method for producing a V-Ti wear-resistant steel with a hardness of HB550-600 as claimed in claim 5, characterized in that: The cooling temperature is between 899 and 923°C, and the cooling rate is between 79 and 85°C / s.

7. The method for producing a V-Ti wear-resistant steel with a hardness of HB550-600 as claimed in claim 5, characterized in that: During offline quenching: the heating temperature is controlled at 656-665°C at a heating rate of 6-8°C / min; then the heating temperature is controlled at 878-890°C at a heating rate of 28-30°C / min, and the holding time is 5-8min.

Citation Information

Patent Citations

  • A weldable wear-resistant steel of grade HB500 with a thickness of 60-80 mm and its production method

    CN110306110B

  • A high-strength, tough, weldable, corrosion-resistant, and wear-resistant steel plate and its preparation method

    CN113106341B

  • HB500 grade hot continuous rolling high strength wear-resisting steel and production method thereof

    CN103266269A

  • HB600 grade wear-resistant non-quenched and tempered steel plate and making method thereof

    CN104831189A